(untitled) (Justicia &Derecho, 2025)
There have been relevant legislative efforts around the world to promote the inclusion, comprehensive care and protection of the rights of autistic people. One of the most recent cases is Law 21,545 of Chile, published on March 10, 2023. We hypothesize that, despite the above, the autistic population in Chile faces significant obstacles to participating in mediation processes that are mandatory prior to a judicial instance. The critical aspects that could potentially hinder the participation of autistic people in mediation were investigated, considering testimonies and systematization of the process. The results showed that some aspects of mediation theory and installed practices have a neurotypical approach that could hinder the full inclusion of autistic people.